Strengthening the Resilience of Children and Adolescents during a Pandemic: A Scoping Review on Eligible Interventions - Bischops, Anne Christine; Reinauer, Christina; Pischke, Claudia; Mayatepek, Ertan; Meißner, Thomas (Klinische Pädiatrie, 2022)
Background The COVID-19 pandemic dramatically affects children’s and adolescents’ mental health. The accumulation of stress factors and a lack of social support complicate a healthy development. Since the beginning of the pandemic, there has been almost a doubling of mental health problems in children and adolescents. Promoting resilience is a possible approach to reduce the incidence of mental health problems despite these adverse circumstances.Objectives This literature search aims at identifying and evaluating interventions to promote resilience mechanisms, with a special focus on feasibility in a crisis situation.Materials and methods This scoping review is based on a systematic literature search including the databases Cochrane Library, PubMed, Psyc-Info, Psyndex and Google Scholar (2006–2020). Of 1733 identified articles 75 were included.Results Out of 72 identified intervention studies 28% were feasible under pandemic conditions. The most effective resilience trainings seem to be individualized interventions using cognitive behavioral therapy elements. However, many approaches primarily show short-term success.Discussion Few evidence-based programs are feasible online or under pandemic restrictions. Most of them show short-term effects and focus on parents and individuals. Multiple programs are ready for use, but still lack proof of efficacy. The development and improvement of (digital) resilience interventions should be an essential part of preventive health care, especially for risk groups.Hintergrund Die COVID-19-Pandemie beeinflusst die mentale Gesundheit von Kindern und Jugendlichen auf dramatische Weise. Durch eine Akkumulation von Belastungsfaktoren und das Wegfallen sozialer Unterstützung ist eine regelrechte Entwicklung erschwert. Seit Beginn der Pandemie kam es nahezu zu einer Verdopplung der psychischen Auffälligkeiten. Die Förderung der Resilienz kann ein Ansatz sein, das Auftreten von psychischen Auffälligkeiten trotz dieser widrigen Umstände zu vermindern.Ziel der Arbeit Ziel dieser Literaturrecherche ist die Identifikation und Bewertung von Interventionen zur Förderung von Resilienzmechanismen, mit Fokus auf die Durchführbarkeit unter Krisenbedingungen.Material und Methoden Dieses Scoping Review basiert auf einer systematischen Literaturrecherche der Datenbanken Cochrane Library, PubMed, Psyc-Info, Psyndex sowie Google Scholar (2006–2021). Von der insgesamt 1733 Artikel umfassenden Suche wurden 75 Artikel eingeschlossen.Ergebnisse Von 72 identifizierten Interventionsstudien sind 28% unter Pandemiebedingungen durchführbar. Die wirksamsten Resilienztrainings scheinen individualisierte Interventionen mit Elementen der kognitiven Verhaltenstherapie zu sein. Viele Ansätze zeigen jedoch in erster Linie kurzfristige Erfolge.Diskussion Nur wenige evidenzbasierte Programme sind online oder unter Pandemiebedingungen verfügbar. Die meisten von ihnen zeigen kurzfristige Effekte und konzentrieren sich auf Eltern und Einzelpersonen. Zahlreiche Programme sind nutzbar, allerdings fehlt häufig ein Evidenznachweis. Die Entwicklung und Verbesserung von (digitalen) Resilienzmaßnahmen sollte ein wesentlicher Bestandteil der präventiven Gesundheitsversorgung sein, insbesondere für Risikogruppen.
Keywords: COVID-19; Resilience; Intervention; Children; Adolescents; Pandemic